2022
DOI: 10.1371/journal.pone.0270411
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and practices regarding tick-borne diseases among an at-risk population living in Niigata prefecture, Japan

Abstract: Objective This study examined the knowledge, attitudes, and practices (KAP) of an at-risk population living in Niigata prefecture regarding tick-borne diseases (TBDs) and preventive strategies. Methods A cross-sectional questionnaire-based study was conducted to assess the KAP of the community. Results In total, 186 responses were received. Among the respondents, 130 (69·9%) were men, and the mean age was 51.1 (14·3). Nine (4·8%) respondents reported having experienced tick bites. Of the respondents, 44 (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…The model's interpretability exhibited a higher degree of coherence in the overall participant sample as well as in Heilongjiang and Jilin provinces, yet presented a relatively lower coherence in Liaoning province. Notably, the tick bite rate observed in Niigata Prefecture, Japan, during the survey was 4.8% [ 36 ], which is notably similar to the findings of this study. However, a study in Sweden showed that 31% of the respondents report one or more tick bites in the last year [ 37 ].…”
Section: Discussionsupporting
confidence: 87%
“…The model's interpretability exhibited a higher degree of coherence in the overall participant sample as well as in Heilongjiang and Jilin provinces, yet presented a relatively lower coherence in Liaoning province. Notably, the tick bite rate observed in Niigata Prefecture, Japan, during the survey was 4.8% [ 36 ], which is notably similar to the findings of this study. However, a study in Sweden showed that 31% of the respondents report one or more tick bites in the last year [ 37 ].…”
Section: Discussionsupporting
confidence: 87%